MicroRNAs in melanocyte and melanoma biology. (6th January 2015) - Mione, Marina; Bosserhoff, Anja
Summary The importance of microRNAs as key molecular components of cellular processes is now being recognized. Recent reports have shown that microRNAs regulate processes as diverse as protein expression and nuclear functions inside cells and are able to signal extracellularly, delivered via exosomes, to influence cell fate at a distance. The versatility of microRNAs as molecular tools inspires the design of novel strategies to control gene expression, protein stability, DNA repair and chromatin accessibility that may prove very useful for therapeutic approaches due to the extensive manageability of these small molecules. However, we still lack a comprehensive understanding of the microRNA network and its interactions with the other layers of regulatory elements in cellular and extracellular functions. This knowledge may be necessary before we exploit microRNA versatility in therapeutic settings. To identify rules of interactions between microRNAs and other regulatory systems, we begin by reviewing microRNA activities in a single cell type: the melanocyte, from development to disease.